WTO negotiations on trade facilitation self assessment guide 2009- (WTO [Geneva]CH, 2009)
Presents revision based on the Draft Consolidated Negotiating Text. Incorporates Member's proposals on perishable goods and electronic payments.
Documentation Centre has : 2009 rev.3; 2013 rev.4